Considering Effect Of Quality Of Communication And Customer Commitment On Word-Of-Mouth Advertisement Of Customers Of Melli Bank In Rasht City - Zargari, Kamran; Hazraty, Morteza (The Turkish Online Journal of Design Art and Communication, 2016)
Word-of-mouth advertisement is one subject that has attracted attention of many researchers of marketing science and behavior of consumers in recent years. Word-of-mouth advertisement is the phenomenon that has been known for years and it was proved that it is a powerful method at making and stopping business. Word-of-mouth advertisement is the consequence and basis of customer preservation and loyal customers have more tendencies to creating positive word of mouth advertisement and act as follower of business name for company. Therefore the main goal of this research is considering the effect of communication quality and customer commitment on word of mouth advertisement among customers of Melli bank in Rasht city. Therefore current research is applied and regarding classification of research based on the way of data collection it is descriptive. Statistical society of research is all customers using services of Melli bank in Rasht city. Sampling method in current research is available improbable sampling method. Tool of data collection is standard questionnaire. All data analysis was done through SPSS and PLS software. For considering hypothesis of research confirming factor analysis and structural equation modeling have been done through partial minimum square. Result of research denotes positive and meaningful effect of customer satisfaction on reliance, commitment and word of mouth advertisement. In consideration of other hypothesis positive and meaningful effect of customer reliance on commitment and word of mouth advertisement and commitment on word of mouth advertisement has been approved. In this research two moderating hypothesis were identified that mediating role of customer commitment in relationship between reliance and customer satisfaction with word of mouth advertisement were considered that these hypothesis were approved. Finally in latest hypothesis moderating role of tendency to use was considered this hypothesis has been approved.
Keywords: word of mouth advertisement; communication quality; customer commitment; tendency to use; Melli bank